Comparative analysis of lithium-ion and flow batteries for advanced energy storage technologies - Maksudovna Vafaeva Khristina; Sanjeeva P. (MATEC Web of Conferences, 2024)
This research does a thorough comparison analysis of Lithium-ion and Flow batteries, which are important competitors in modern energy storage technologies. The goal is to clarify their unique characteristics and performance measures. Lithium-ion batteries demonstrate superior energy density (200 Wh/kg) and power density (500 W/kg) in comparison to Flow batteries (100 Wh/kg and 300 W/kg, respectively), indicating their ability to store more energy per unit mass and provide higher power outputs. Flow batteries have a competitive advantage in terms of cycle life, providing a longer duration of 1000 cycles compared to Lithium-ion batteries, which only offer 500 cycles. In addition, although Lithium-ion batteries have a higher efficiency of 90% compared to 80% in Flow batteries, the latter exhibit a lower environmental impact with decreased CO2 emissions (30 g/kWh) and a lower toxicity rating. Lithium-ion batteries have lower material costs, amounting to $200 per kilowatt-hour (kWh). However, they entail higher installation costs of $5000 and maintenance costs of $200, when compared to Flow batteries, which have material costs of $150/kWh, installation costs of $8000, and maintenance costs of $300. In addition, Lithium-ion batteries demonstrate superior charging capabilities of 50 kW and discharging rates of 70 kW, surpassing Flow batteries which have charging rates of 30 kW and discharging rates of 40 kW, respectively. The findings of this study highlight the subtle advantages and compromises of Lithium-ion and Flow batteries in terms of different performance parameters. This information is crucial for making well-informed decisions when choosing energy storage technologies that meet specific application needs in a wide range of sectors, including portable electronics and grid-scale applications.